Pengaruh Financial Attitude, Financial Behavior, Financial Knowledge, dan Risk Tolerance terhadap Financial Satisfaction - Olivia Sandra Wijaya; Ary Satria Pamungkas (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this study is to examine the effect of Financial Attitude, Financial Behavior, Financial Knowledge and Risk Tolerance on Financial Satisfaction. The sample in this study is all residents who already have income or income in the Jakarta area. The sample was chosen by the non-probability sampling method, amounting to 190 respondents by distributing questionnaires online. The data analysis technique used is Structural Equation Modeling (SEM) which is assisted with the assistance of the Smart-PLS program.3.3.2. The results of this study are that there is a positive influence of Financial Attitude on Financial Satisfaction, there is a positive influence of Financial Behavior on Financial Satisfaction, and there is a positive influence of Financial Knowledge on Financial Satisfaction. While the results obtained in this study indicate there is no effect of Risk Tolerance on Financial Satisfaction. Tujuan dari penelitian ini adalah untuk meneliti mengetahui pengaruh Financial Attitude, Financial Behavior, Financial Knowledge dan Risk Tolerance terhadap Financial Satisfaction. Sampel pada penelitian ini adalah seluruh penduduk yang sudah memiliki pendapatan atau penghasilan di wilayah Jakarta. Sampel dipilih dengan metode non-probability sampling yang berjumlah 190 responden dengan penyebaran kuesioner secara online. Teknis analisis data digunakan adalah Structural Equation Modeling (SEM) yang dibantu dengan bantuan program Smart-PLS.3.3.2. Hasil dari penelitian ini adalah terdapat pengaruh positif Financial Attitude terhadap Financial Satisfaction, terdapat pengaruh positif Financial Behavior terhadap Financial Satisfaction, dan terdapat pengaruh positif Financial Knowledge terhadap Financial Satisfaction. Sedangkan hasil yang didapat pada penelitian ini menunjukkan tidak terdapat pengaruh Risk Tolerance terhadap Financial Satisfaction.